INDIGENISMO AND THE LIMITS OF CULTURAL APPROPRIATION: frida kahlo and marina núñez del prado. Issue 3 (4th July 2022) - Sutherland, Camilla
Abstract: This article turns a critical eye on the indigenista movement that flourished in Latin America in the first half of the twentieth century, specifically as it relates to gender, race, and the visual arts. Beginning with a brief overview of the emergence of indigenismo in Mexico and the Andean region, it will move on to offer a comparative reading of the life and works of Mexican painter Frida Kahlo (1907–54) and the lesser-known Bolivian sculptor Marina Núñez del Prado (1910–95). Both women drew heavily from indigenous culture in their works and employed modes of self-fashioning rooted in performed indigeneity. As members of a cosmopolitan elite, Kahlo's and Núñez del Prado's engagements with indigenous culture can be framed as appropriative. However, what this article seeks to explore is the extent to which gender and location complicate our interpretation of the racial tensions at the heart of Latin American modernism.